THE RESULTS OF WORK OF THE EXPERT COMMISSION ON THE SELECTION OF CANDIDATES FOR SCHOLARSHIP OF THE PRESIDENT AND THE GOVERNMENT OF THE RUSSIAN FEDERATION FOR GRADUATE STUDENTS - Irina A. Mosicheva; Marina V. Sokolova; Albina A. Chervova; Evgeniy V. Chuprunov (Высшее образование в России)
The article highlights the results of the work of expert commission on the selection of candidates for scholarship of the President and the Government of the Russian Federation for post(graduate students in Academic Year 2014/15. Some academic and research achievements of the contestants are adduced. Special attention is paid to the shortcomings in contestants’ registration materials and to the recommendation for improvement of the candidates’ selection system.